Privacy leakage in online social networks based on public information - Shao-qing LV; Yu-qing ZHANG; Ping NI (Tongxin xuebao)
An algorithm was proposed to predict privacy information in social network with public information. This al-gorithm detected communities in the friend relationship network and inferred privacy information using public informa-tion of some friends. The results show that users' privacy information can be estimated with high accuracy when given only a little public information.